Disparities of infant and neonatal mortality trends in Greece during the years of economic crisis by ethnicity, place of residence and human development index: a nationwide population study. Issue 8 (17th August 2019) - Siahanidou, Tania; Dessypris, Nick; Analitis, Antonis; Mihas, Constantinos; Evangelou, Evangelos; Chrousos, George; Petridou, Eleni
Abstract : Objective: To study trends of infant mortality rate (IMR) and neonatal mortality rate in Greece during the period 2004–2016 and explore the role of sociodemographic factors in the years of crisis. Design: Nationwide individual data for live births and infant (0–11 months) deaths provided by the Hellenic Statistical Authority were examined using Poisson, joinpoint regression and interrupted time series (ITS) analyses. Setting: Greece. Participants: All infant deaths (n=4862) over the 13-year period, of which 87.2% were born to Greek mothers, and respective live births. Main outcome measures: Evolution of IMR (0–364 days), early (<7 days) neonatal mortality rate (ENMR), late (7–27 days) neonatal mortality rate (LNMR) and post neonatal (28–364 days) mortality rate (PNMR) trends, by maternal nationality, place of residence and Human Development Index (HDI). Results: By Poisson regression, overall, during the study period, among infants of Greek mothers, IMR and PNMR declined significantly (−0.9%; 95% CI −1.7% to −0.1% and −1.6%; −3.0% to −0.2% annually, respectively), although differentially by place of residence (IMRurban : −2.1%; −2.9% to −1.3%, IMRrural : +10.6%; 7.6% to 13.6%). By contrast, among infants of non-Greek mothers, the low starting IMR/ENMR/LNMR/PNMR increased significantly (max ENMR:+12.5%; 8.6% to 16.5%) leading to a non-significant time–trend pattern overall in Greece. The inverse associations of HDI with IMR, ENMR and PNMR were restricted to Greek mothers' infants. Joinpoint regression analyses among Greek mothers' infants indicated non-significant increasing trends of IMR and ENMR following the crisis (+9.3%, 2012–2016, p=0.07 and +10.2%, 2011–2016, p=0.06, respectively). By contrast, the high (+17.1%; 8.1% to 26.9%, p=0.002) IMR increases among non-Greek infants were restricted to 2004–2011 and equalised to those of Greek mothers' infants thereafter. ITS analyses in preset years (2008, 2010, 2012) identified significantly increasing trends in IMR, LNMR and PNMR after 2012, and in ENMR after 2010, among Greek mothers' infants. Conclusions: HDI and rural residence were significantly associated with IMR. The strongly decreasing IMR trends among Greek-mothers' infants were stagnated after a lag time of 4 years of crisis approximating the previously sharply increasing trends among non-Greeks.